THE EFFECTIVENESS OF THE IMPLEMENTATION OF DISABILITY-FRIENDLY TOURISM ACCESSIBILITY FULFILLMENT PROGRAM IN THE CITY OF SURAKARTA - Syahira Khansa Nafidiin; Sulistiya Anggraeni; Zahro’ Nur Aini; Roviq Nur Vadila; Falah Qurrota Ayun; Elizabeth Nababan; Ega Istiawan (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2026)
The implementation of inclusive tourism in the city of Surakarta still faces various challenges even though it has been supported by regulations that regulate the protection and fulfillment of the rights of persons with disabilities. This research aims to evaluate the effectiveness of the implementation of disability-friendly tourism accessibility, identify the role of stakeholders, and analyze various challenges in realizing inclusive tourism in the city of Surakarta. This study used mixed methods with the CIPPO evaluation model through the distribution of questionnaires to 96 people with disabilities and in-depth interviews with relevant stakeholders. The results of the study show that the implementation of tourism accessibility policies is in the category of sufficient with an index of 2.35. Physical accessibility obtained an index of 2.93, service quality of 2.67, and information and communication accessibility of 2.55, all of which were in the sufficient category. The fulfillment of accessibility is carried out through the collaboration of various stakeholders, namely the Culture and Tourism Office, Bappeda, DPUPR, Social Service, Transportation Office, and Regional Disability Committee. Although accessibility facilities have been made available in several tourist destinations, their implementation still faces obstacles in the form of limited budget and human resources, low participation of communities with disabilities, weak coordination between stakeholders, and low public awareness of the importance of accessibility. Therefore, it is necessary to strengthen collaboration and involve people with disabilities in a sustainable manner to realize more inclusive tourism in the city of Surakarta. Keywords: inclusive tourism, accessibility, people with disabilities, stakeholders, policy evaluation.